STANDARISASI INSTRUMEN INTEGRATED ASSESSMENT HASIL BELAJAR BAHASA DENGAN PROGRAM QUEST - Pujiati Suyata; Nur Hidayanto; Agus Widyantoro (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to produce a model of standardized convergent and divergentintegrated-assessment instruments for Indonesian and English learning outcomes atjunior high schools using Item Response Theory. It employed a research and developmentdesign. In the first year, a learning continuum was developed, followed by the developmentof integrated assessment instruments based on the learning continuum. Instrumentstandardization was then conducted using 1-PL Item Response Theory and the QUESTprogram. The results of the first year were 30 standardized integrated assessmentinstrument sets, a guidebook for construction of the integrated assessment instruments forlanguage learning outcomes and the QUEST program guidebook. In the second year, theintegrated assessment instruments for language learning outcomes were disseminated inprovinces of Yogyakarta Special Territory, South Kalimantan, and West Nusa Tenggara.